2019
DOI: 10.1111/nph.15857
|View full text |Cite
|
Sign up to set email alerts
|

Using a reaction‐diffusion model to estimate day respiration and reassimilation of (photo)respired CO2 in leaves

Abstract: Summary Methods using gas exchange measurements to estimate respiration in the light (day respiration ) make implicit assumptions about reassimilation of (photo)respired CO 2 ; however, this reassimilation depends on the positions of mitochondria. We used a reaction‐diffusion model without making these assumptions to analyse datasets on gas exchange, chlorophyll fluorescence and anatomy for tomato leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Berghuijs et al . (2019) showed that R d estimated by the Kok method was closer to the estimate made by their model (that accounted for the refixation) under nonphotorespiratory than under photorespiratory conditions. The experiment of Loreto et al .…”
Section: Discussionmentioning
confidence: 83%
“…Berghuijs et al . (2019) showed that R d estimated by the Kok method was closer to the estimate made by their model (that accounted for the refixation) under nonphotorespiratory than under photorespiratory conditions. The experiment of Loreto et al .…”
Section: Discussionmentioning
confidence: 83%
“…Berghuijs et al . (2019) elaborated on the 2D model of photosynthetic cells described in Berghuijs et al . (2017) and used observed values of A to predict maximal carboxylation ( V cmax ) and R light by fitting.…”
Section: How To Measure Rlight?mentioning
confidence: 99%
“…One advantage of this technique is that it is independent of g m , thus providing a way of estimating R light , and in turn, assisting in calculating values of g m and c c . Berghuijs et al (2019) elaborated on the 2D model of photosynthetic cells described in Berghuijs et al (2017) and used observed values of A to predict maximal carboxylation (V cmax ) and R light by fitting. This technique assumes a certain geometry of the…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photorespiration has been seen as a wasteful process since it leads to a potential loss of assimilated carbon and nitrogen and it has an energetic cost since released CO 2 can diffuse to the chloroplast to be re-assimilated [ 6 ] and photorespiratory NH 3 can be re-assimilated by the glutamine synthase/glutamine:2-oxoglutarate aminotransferase (GS/GOGAT) cycle [ 7 ]. However, photorespiration is crucial for plant growth in air as seen from studies of photorespiratory mutants that exhibit various deleterious symptoms including dwarfism, chlorosis, and plant death [ 8 ].…”
Section: Introductionmentioning
confidence: 99%